Effect of nephrology follow‐up on long‐term outcomes in patients with acute kidney injury: A systematic review and meta‐analysis. Issue 8 (18th February 2020) - Ye, Nan; Xu, Ying; Bellomo, Rinaldo; Gallagher, Martin; Wang, Amanda Y.
Abstract: Aim: Acute kidney injury (AKI) is associated with poor short‐term and long‐term clinical outcomes. The role of nephrology follow‐up in post‐AKI management remains uncertain. Methods: A systematic review and meta‐analysis were performed examining all randomized controlled trials and observational studies assessing the effect of nephrology follow‐up on patients' clinical outcomes. The primary outcome was all‐cause mortality. The secondary outcomes were renal outcomes, which were defined as a composite of requirement of permanent dialysis and recurrent AKI. Pooled analysis was performed using a random‐effect model. Results: We identified six studies (8972 patients, mean follow‐up of 49 months). Five were retrospective cohort studies and one was a prospective cohort study. Risk of bias was a concern with all studied. Only four studies reported primary and/or secondary outcomes and were included. Compared with patients without nephrology follow‐up, patients with nephrology follow‐up had significantly reduced mortality by 22% (three studies, 3240 patients, relative risk [RR] = 0.78, 95% confidence interval [CI] = 0.70‐0.88, I 2 = 0.0%). Nephrology follow‐up did not improve composite renal outcomes with high heterogeneity due to significant differences in reported renal outcomes and follow‐up period (two studies, 2537 patients, RR = 1.72, 95% CI = 0.49‐6.05, I 2 = 90.1%). Conclusion: Current evidence from observational studies is biased. It suggests long‐term survival benefits with post‐discharge nephrology follow‐up in AKI patients. However, due to its low quality, such evidence is only hypothesis‐generating. Nonetheless, it provides a rationale for future randomized controlled trials of nephrology follow‐up in AKI patients. SUMMARY AT A GLANCE The present meta‐analysis assessed the effect of nephrology follow‐up on patients' clinical outcomes, and suggested long‐term survival benefits in acute kidney injury (AKI) survivors. Although the study inherently comprises potential risks of bias due to paucity of available data, the results provide a rationale for future randomized controlled trials.